E-LEARNING SATISFACTION ANALYSIS OF CLINICAL ROTATION NURSING STUDENTS - Totok Harjanto; Bayu Fandhi Achmad; Dimas S. E. W. Sumunar (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2023)
ABSTRACTObjective: To identify the learning satisfaction of clinical rotation nursing management students. Methods: A descriptive study took place in a class of clinical rotation nursing management. Participants were 22 female clinical rotation nursing student who were in the nursing management stage period September-October 2017. Eligible criteria for the students are voluntary participating in the research, fully engaged in the whole learning activities and following brief introduction and course evaluation. Research instrument is the form of learning satisfaction questionnaire developed by Center of Innovation and Academic Policy UGM. Validity test incorporate product moment resulting 13 valid items. 10 items required modification to meet the validity. Cronbach’s Alpha reliability test yields internal consistency value of 0.839. Data analyses were using frequency distribution with means considered as cutoff point. Results: Clinical rotation nursing students have a similar learning satisfaction between high and low (50%: 50%). Discussion: Based on 4 attributes of the questionnaire, the majority of respondents have high satisfaction on the aspect of online assignment (54.5%), aspect of online lecture materials and eLearning facilities have the same satisfaction (50%: 50%) and the online discussion aspect of the majority of respondents have low satisfaction (54.5 %). Conclusion: Clinical rotation students in nursing management show the same level of satisfaction between high and low on e-learning. Development of learning media and electronic learning delivery methods required to value the benefits in the future.Keywords: clinical rotation; e-learning; nursing student; students’ satisfaction.